The prevalence of loot boxes in mobile and desktop games. (6th February 2020) - Zendle, David; Meyer, Rachel; Cairns, Paul; Waters, Stuart; Ballou, Nick
Abstract: Background and Aims: Loot boxes are items in video games that may be bought for real‐world money but provide randomized rewards. Formal similarities between loot boxes and gambling have led to concerns that they may provide a 'gateway' to gambling amongst children. However, the availability of loot boxes is unclear. This study aimed to determine what proportion of top‐grossing video games contained loot boxes, and how many of those games were available to children. Design, setting and cases: Survey of the 100 top‐grossing games on both the Google Play store and the Apple App store, and the top 50 most‐played games on Steam according to the data aggregator SteamSpy. Measurements: The prevalence of loot boxes was measured for each platform outlined above, split by age rating. Findings: A total of 58.0% of the top games on the Google Play store contained loot boxes, 59.0% of the top iPhone games contained loot boxes and 36.0% of the top games on the Steam store contained loot boxes; 93.1% of the Android games that featured loot boxes and 94.9% of the iPhone games that featured loot boxes were deemed suitable for children aged 12+. Age ratings were more conservative for desktop games. Only 38.8% of desktop games that featured loot boxes were available to children aged 12+. Conclusions: Loot boxes appear to be prevalent in video games that are deemed suitable for children, especially on mobile platforms.